Digital Remedy: A Prophylaxis for Business Failure in Emerging Markets - Dikeledi Jacobeth Warlimont; Ifeanyichukwu Ojeka Ukonu (Ovidius University Annals: Economic Sciences Series)
The introductory phase is a critical stage in the growth and development of any small business. Past studies have reported a high mortality rate of SMEs within the first few years of commencing business operations. With the advent of technology in the rapidly advancing business scenario, digital tools and strategies are increasingly identified as essential for business survival and growth. Methodologically, the study adopted secondary data to proffer an all-inclusive and comprehensive technique to comprehend how digital remedies can be prophylaxis (preventive measure) against business mortality using secondary data from academic journals, industry reports and peer-reviewed articles on digital transformation and highlighted causes of business failures. This study forms a bedrock for a more indepth analysis of digital resolutions, such as data analysis, artificial intelligence AI, automation, cloud computing, digital marketing, and advertisement, as prophylaxis or preventive measures for common causes of business failure. The findings of a more comprehensive study will provide insight for stakeholders desiring to alleviate risks, enhance operations, and remain competitive in an ever-evolving digital economy.